PENGARUH KEPEMILIKAN KELUARGA TERHADAP TAX AVOIDANCE DENGAN VOLUNTARY DISCLOSURE SEBAGAI VARIABEL MODERASI (Studi Empiris pada Perusahaan Sektor Barang Konsumen Primer yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2021) - Kreativa, Angela Twinda; Prabowo, Tri Jatmiko Wahyu (Diponegoro Journal of Accounting, 2024)
This study aims to examine the effect of family ownership on tax avoidance with voluntary disclosure as a moderating variable in consumer non-cyclicals companies listed on the Indonesia Stock Exchange (IDX) for the period 2019-2021. Tax avoidance is the dependent variable, measured using the Effective Tax Rate (ETR), while family ownership serves as the independent variable, and voluntary disclosure serves as the moderating variable. Control variables encompass company size, profitability measured by Return on Assets (ROA), leverage, and year dummies.The research population consists of companies in the consumer non-cyclicals sector that were listed on the IDX during the period 2019-2021. Employing purposive sampling, 87 research samples were selected for analysis. Panel data regression, specifically utilizing the Random Effects Model (REM), was employed to assess the relationships among these variables.The research results indicate a positive influence of family ownership on tax avoidance. It was also found that the voluntary disclosure variable is able to weaken the positive influence of family ownership on tax avoidance.